2012
DOI: 10.1590/s1415-47572012000400012
|View full text |Cite
|
Sign up to set email alerts
|

Demarcation of informative chromosomes in tropical sweet corn inbred lines using microsatellite DNA markers

Abstract: A study of genetic variation among 10 pairs of chromosomes extracted from 13 tropical sweet corn inbred lines, using 99 microsatellite markers, revealed a wide range of genetic diversity. Allelic richness and the number of effective alleles per chromosome ranged from 2.78 to 4.33 and 1.96 to 3.47, respectively, with respective mean values of 3.62 and 2.73. According to the Shannon’s information index (I) and Nei’s gene diversity coefficient (Nei), Chromosome 10 was the most informative chromosome (I = 1.311 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Molecular markers are used for the characterization of germplasms, identification and mapping of genes and QTLs for various agriculturally important traits in maize [ 31 , 32 , 33 , 34 , 35 , 36 ]. A previous study identified four simple sequence repeat (SSR) markers linked to the sh2 gene via bulk-segregant analysis (BSA) in three mapping populations [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers are used for the characterization of germplasms, identification and mapping of genes and QTLs for various agriculturally important traits in maize [ 31 , 32 , 33 , 34 , 35 , 36 ]. A previous study identified four simple sequence repeat (SSR) markers linked to the sh2 gene via bulk-segregant analysis (BSA) in three mapping populations [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, phenotypic traits are influenced by environmental factors. In contrast, molecular markers are not and can be used to detect genetic diversity among inbred lines and to predict hybrid performance and heterosis (Kashiani et al, 2012;Solomon et al, 2012). An important aspect of hybrid and inbred line development is having information about the genetic diversity and the genetic relationship among inbred lines.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several years, sweet corn production improvements in Brazil have consisted of obtaining hybrids (Kwiatkowski et al, 2011) and assessing diverse germplasm (Almeida et al, 2011;Terra et al, 2011) to form a broad genetic basis for local farmers. Information about genetic diversity in corn is essential to germplasm characterization and utilization (Gerdes and Tracy, 1994;Kashiani et al, 2012;Liu et al, 2003;Nigussie and Saleh, 2007;Revilla et al, 2005;Srdić et al, 2011;Tracy et al, 2000;Yousef and Juvik, 2001), particularly among the sul germplasm from southern Brazil (Amorin et al, 2003;Barbosa-Neto et al, 2005;Bered et al, 2005;Rupp et al, 2009). The number of investigations can be considered limited when compared to the number of varieties available with the potential to be used for breeding programs.…”
Section: Introductionmentioning
confidence: 99%